(3GdahGFO GdVjGFjIs - (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s
(3ChdgG (B:s
(3GdMeO dhdjg hGdUdGI Ydi fHjg eMeO hYdi Bdg hCUMGHg GdeJCOHjf HBOGHg CeG HYO agPg ahGFO hGajI HMd eTcdGJ GdcGajI s
(3BNQgG (B:s
(3hUd Ydi ef TaGYJg ai eMh CQbGe GdVdGdGJ cGajI hYf eVQI CSbGe GdLgdGJ TGajI hYdi Bdg hCUMGHgq s
(3GdfSNI HgG MhGTs
(3GdfU TQM dcGajI GHf GdMGLH GdeJhai (B646 (3g`s
(3HgG LOGhd JhVjMjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs